(untitled) (Polis (Santiago), 2018)
In this article we work starting from the ethnographic evidence about the propensity to learn that children of four and five years of age have, who attend two marginal urban schools in the cities of La Serena and Coquimbo, Chile. We establish some criteria to support the existence of a tendency to learn. The observation has been focused specifically on informal interactions and not intentional pedagogical action of professional educators, because we are interested in revealing how they learn among them organizing emerging learning processes. The findings suggest that children cannot help to learn and that they do it very well, without in almost all cases even aiming intentionally to learn. Also they use perfectly rigorous and demanding experimentation, logical reasoning and contrasting, as any scientist in his task, far surpassing any formal learning promoted in kindergarten. From these findings we believe that the crisis affecting school can be overcome if we consider the infinite potential of the propensity to learn, since self-organizing flows following simple patterns yet at the same time complex.